2021
DOI: 10.3390/cancers13112588
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenesis of Triple-Negative Breast Cancer and Sex Steroid Hormones

Abstract: Triple-negative breast cancer (TNBC) lacks an effective treatment target and is usually associated with a poor clinical outcome; however, hormone unresponsiveness, which is the most important biological characteristic of TNBC, only means the lack of nuclear estrogenic signaling through the classical estrogen receptor (ER), ER-α. Several sex steroid receptors other than ER-α: androgen receptor (AR), second ER, ER-β, and non-nuclear receptors represented by G-protein-coupled estrogen receptor (GPER), are frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…Androgen activation or expression can be upregulated, leading to tumorigenesis through genomic signaling. 30 The early onset of TNBC that is androgen receptor positive can be associated with higher serum levels of estrogen/androgen in premenopausal women. 30 Estrogen's role, in particular, has significant downstream effects.…”
Section: Georgetown Medical Review Hormone Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Androgen activation or expression can be upregulated, leading to tumorigenesis through genomic signaling. 30 The early onset of TNBC that is androgen receptor positive can be associated with higher serum levels of estrogen/androgen in premenopausal women. 30 Estrogen's role, in particular, has significant downstream effects.…”
Section: Georgetown Medical Review Hormone Metabolismmentioning
confidence: 99%
“…30 The early onset of TNBC that is androgen receptor positive can be associated with higher serum levels of estrogen/androgen in premenopausal women. 30 Estrogen's role, in particular, has significant downstream effects. In oral contraceptive use, it can stimulate angiogenesis, ER binding, and stromal cell recruitment leading to cancer development.…”
Section: Georgetown Medical Review Hormone Metabolismmentioning
confidence: 99%
“…This classification is based on genetic profiles dividing TNBC into basal-like 1 (BL1), basallike 2 (BL2), immunomodulatory (IM), mesenchymal (M), mesenchymal stem like (MSL) and luminal androgen receptor (LAR) subtypes [13,14]. Although TNBC is characterized by the lack of expression of ERα, PR and HER-2 overexpression, this breast cancer subtype is capable of expressing other receptors like the androgen receptor (AR) or the estrogen receptor β (ERβ) [8,15,16]. The AR is present in around 10-43% of cases of TNBC [8,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the AR has been postulated to be a promising target for future therapies against TNBC [11]. On the other hand, ERβ has been of interest because of its presence in around 30% of TNBC cases [15,16]. The ERβ role in TNBC is controversial among research; however, it has been observed to be clearly involved in TNBC development processes [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation